2017
DOI: 10.1039/c7ra02278f
|View full text |Cite
|
Sign up to set email alerts
|

The supranutritional selenium status alters blood glucose and pancreatic redox homeostasis via a modulated selenotranscriptome in chickens (Gallus gallus)

Abstract: Dietary Se status stabilizes pancreatic normal physiology functionviathe regulation of the selenoprotemic transcriptions. Supranutritional or excess Se status alters the pancreatic redox homeostasisviamodulated selenotranscriptome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…insulin resistance, hyperglycemia, and high low-density lipoproteins. These results correspond to Xiang et al (2017) that additional Se as dietary feeding with high level (5 mg/ kg) was high blood glucose, whereas at lower concentration (3 mg/kg) lower blood glucose was observed.…”
Section: Discussionsupporting
confidence: 88%
“…insulin resistance, hyperglycemia, and high low-density lipoproteins. These results correspond to Xiang et al (2017) that additional Se as dietary feeding with high level (5 mg/ kg) was high blood glucose, whereas at lower concentration (3 mg/kg) lower blood glucose was observed.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, 24 selenoproteins and associated transcription factors were influenced by Se intake in chickens’ pancreas. Selenium contributions to chicken development and regulation of blood sugar were associated with pancreatic redox homeostasis via a modulated selenotranscriptome [ 137 ]. Selenoprotein genes in spleen and thymus were down-regulated, inflammation-related genes were up-regulated due to supranutritional dietary Se status.…”
Section: Effects Of Selenium Supplementation In Chickenmentioning
confidence: 99%
“…The animal models play an important role in exploring the mechanisms associated with type 2 diabetes. Several studies have evaluated the influence of Se (IV) intake on blood glucose and insulin levels as well as pancreatic function in animal models [ 59 61 ]. In recent years, the scientific focus has been switched towards selenium nanoparticles as they have impressive therapeutic effects due to better production of reactive oxygen species in a dose-dependent manner, compared to selenite [ 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has to be noted that some studies showed a negative association between selenium and the symptoms of type 2 diabetes [ 78 ]. The increased blood glucose levels and the decrease in pancreatic antioxidant capacity were observed when chickens were fed with a high dose of selenite (5.0 mg/kg) for 8 weeks, but the opposite results were obtained when a lower dose (3 mg/kg) was applied [ 59 ].…”
Section: Introductionmentioning
confidence: 99%